PENGARUH KOMITE AUDIT, RETURN ON ASSETS (ROA), DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK - Fabia Tiala; Ratnawati Ratnawati; M.Taufiq Noor Rokhman (Politeknik Ubaya, 2019)
This study aims to test and describe Tax Avoidance which is influenced by the Audit Committee, Return On Assets (ROA), and Leverage. This study uses two variables, namely the independent and dependent variables, and the source of data in this study in the form of financial statements of mining sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2015-2017. Data analysis was performed by classical assumption test and hypothesis testing in this study using multiple linear regression methods. The results of this study indicate that partially the Audit Committee and Leverage variables have a significant effect on tax avoidance, while the Return on Assets (ROA) does not affect tax avoidance.